U.S. War in Afghanistan: From Intervention to Counterinsurgency - Dr. Shahid Ahmed Afridi; Marium Fatima (Journal of Political Studies, 2020)
US military intervention in Afghanistan was decisive and forceful, however, the Taliban’s insurgency inevitably transformed U.S. military doctrine and strategy from conventional military intervention into Counterinsurgency’s kinetic and non-kinetic operations. U.S. strategic and operational methodology despite exhausting all possibilities; troops’ surge, air dominance/surveillance, non-kinetic peace building operations, failed to dislodge the threat of Taliban violence. An effort is made to identify the underlying factors contributory to the failure of the U.S. strategy, tactics and other challenges faced despite having unparalleled military superiority. This paper further probes the U.S. military strategic repositioning, social structure with the warlords and critically examines how the conflict drifted from intervention into Counterinsurgency irregular warfare.